Behavioural and objective vestibular assessment in persons with osteoporosis and osteopenia: a preliminary investigation - Gargeshwari,Aditi (2018)
Abstract Introduction: Calcium is vital for the functioning of the inner ear hair cells as well as for the neurotransmitter release that triggers the generation of a nerve impulse. A reduction in calcium level could therefore impair the peripheric vestibular functioning. However, the outcome of balance assessment has rarely been explored in cases with osteopenia and osteoporosis, the medical conditions associated with reduction in calcium levels. Objective: The present study aimed to investigate the impact of osteopenia and osteoporosis on the outcomes of behavioural and objective vestibular assessment tests. Methods: The study included 12 individuals each in the healthy control group and osteopenia group, and 11 individuals were included in the osteoporosis group. The groups were divided based on the findings of bone mineral density. All the participants underwent behavioural tests (Fukuda stepping, tandem gait and subjective visual vertical) and objective assessment using cervical and ocular vestibular evoked myogenic potentials. Results: A significantly higher proportion of the individuals in the two clinical groups' demonstrated abnormal results on the behavioural balance assessment tests (p < 0.05) than the control group. However, there was no significant difference in latencies or amplitude of cervical vestibular evoked myogenic potential and oVEMP between the groups. The proportion of individuals with absence of ocular vestibular evoked myogenic potential was significantly higher in the osteoporosis group than the other two groups (p < 0.05). Conclusion: The findings of the present study confirm the presence of balance-related deficits in individuals with osteopenia and osteoporosis. Hence the clinical evaluations should include balance assessment as a mandatory aspect of the overall audiological assessment of individuals with osteopenia and osteoporosis.